Pengaruh Kompetensi, Kompensasi dan Komitmen Organisasi Terhadap Kinerja Karyawan - Ayu Fil Akhirati; Finnah Fourqoniah (Jurnal Ecogen, 2023)
The success of a company can be judged by the level of performance in managing its human resources. When employee performance is managed properly, it will help achieve business standards and provide maximum benefits for the company. The objectives of this research is to determine the extent to which competence, compensation, and organizational commitment influence employee performance. The research was conducted at the company PT Trisensa Mineral Utama in Kutai Kartanegara with associative quantitative methods. The entire population is used as a sample because the number is small, namely 60 employees. Data collection techniques were obtained from the result of distributing questionnaires, observations, and interview. As for testing the data using the help of IBM SPSS 27 software with analysis techniques including instrument testing, classical assumption testing, multiple linear regression testing, and hypothesis testing. The results showed that both partially and simultaneously the competency, compensation, and organizational commitment variables had a significant effect on employee performance at PT Trisensa Mineral Utama.